2018
DOI: 10.5505/tjtes.2018.32627
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the compliance between EEG monitoring (Bispectral IndexTM) and Ramsey Sedation Scale to measure the depth of sedation in the patients who underwent procedural sedation and analgesia in the emergency department

Abstract: BACKGROUND: This study aimed to investigate the compliance between electroencephalogram monitoring (Bispectral Index, BIS) and Ramsay Sedation Scale (RSS) to measure the depth of sedation in patients who underwent procedural sedation and analgesia (PSA) in an emergency department. This study also aimed to investigate the usefulness of this compliance for early diagnosis of complications. METHODS: A total of 54 consecutive patients during PSA in the emergency department were included in this study. The BIS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…The shape of brain wave shows the spontaneous and rhythmic electrical activity of brain cell group, which is generally described by the characteristics of amplitude, frequency, and phase. During general anesthesia, EEG frequency changes sequentially with the deepening or shallowing of anesthesia and has a functional relationship with anesthetic concentration, so it can be used to reflect the depth of anesthesia [ 11 ]. However, in the early stage, the time-domain characteristics of EEG were mostly used to reflect the depth of anesthesia, mainly analyzing the geometric properties of EEG waveform.…”
Section: Related Workmentioning
confidence: 99%
“…The shape of brain wave shows the spontaneous and rhythmic electrical activity of brain cell group, which is generally described by the characteristics of amplitude, frequency, and phase. During general anesthesia, EEG frequency changes sequentially with the deepening or shallowing of anesthesia and has a functional relationship with anesthetic concentration, so it can be used to reflect the depth of anesthesia [ 11 ]. However, in the early stage, the time-domain characteristics of EEG were mostly used to reflect the depth of anesthesia, mainly analyzing the geometric properties of EEG waveform.…”
Section: Related Workmentioning
confidence: 99%
“…Avci S et al predicted an average BIS score of 70.8 for predicting the associated complications. 12 We observed only a few untoward events at a BIS range of 76-94, none requiring any intervention. The included patients belonged to the non-geriatric age group and had no systemic comorbidities.…”
Section: Discussionmentioning
confidence: 60%
“…These results are in coherence with previous trial conducted to evaluate the compliance between the BIS and RSS under the different settings. 12 The effect of baseline characteristics, especially age on the BIS values for a particular depth of sedation, has not been well addressed. Katoh et al showed that BIS at which response to verbal commands was suppressed is not affected by the age of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Local anesthesia employed in such way decreases the painful stimulus during the procedure and simplifies the medical anesthesia, aiming to keep the patient at a sedation level commensurate with a level 3 on the Ramsay scale, which has been reported to achieve better anxiolysis and intra-and postoperative analgesia. 39…”
Section: Patient Positioning and Anesthesiamentioning
confidence: 99%